The Effect of Peer Education on Decision-Making, Smoking-Promoting Factors, Self-Efficacy, Addiction, and Behavior Change in the Process of Quitting Smoking of Young People - Orsal O; Ergun A (Dove Medical Press, 2021)
Ozgul Orsal,1 Ayse Ergun2 1Eskisehir Osmangazi University, Faculty of Economics and Administrative Sciences, Department of Business/Department of Management and Organization, Eskisehir, Turkey; 2Marmara University Faculty of Health Sciences Department of Nursing, Istanbul, TurkeyCorrespondence: Ozgul OrsalFaculty of Economics and Administrative Sciences, Department of Business/Department of Management and Organization, Eskisehir Osmangazi University, Eskisehir, TurkeyEmail o.orsal222@hotmail.comPurpose: The study aims to examine the effect of peer education on the decision to quit smoking, factors that encourage smoking, self-efficacy, addiction, and behavior change in students who apply to the Youth Friendly Center to quit smoking.Participants and Methods: This research is a Randomized Controlled Trials study. The experimental group consisted of students who were enrolled in the peer education course (n=759). The control group has consisted of students (n=1095) who did not enroll in this course.Results: Participants in the experimental group to quit smoking, more than the control group (p> 0,01). The addiction level of the participants in the experimental group, less than the participants in the control group (p> 0,01). According to the scores of the participants in the control group of the participants in the experimental group, the factors that trigger smoking, and the benefit sub-dimension scores in the Decision Balance Scale were low. Loss sub-dimension scores, which show the losses from the harms of smoking, increased significantly in the Self-Efficacy Scale, Behavior Change Process Scale, and Decision Balance Scale (p> 0,01).Conclusion: Peer educators trained by the researcher and her team in the Youth Friendly Center Smoking Quit Program have an important effect in supporting/improving the cognitive and behavioral change processes of university students in smoking quit compared to those who do not receive an education. 94% success of the smoking quit program; Students’ voluntary application to receive professional support, students’ voluntary attendance of the treatment program for 6 months, strong communication and feedback, effective and functional professional counseling, and social support depend on strengthening the program with peer education. Especially with peer education, the development of leadership and role model characteristics made the smoking quit program preferred by students.Keywords: health promotion and risk management, youth-peer education, smoking quit, randomized controlled trial, university student, youth studies, cognitive/behavioral processes